Political instability and inflation volatility - Veiga, Francisco José (2006)
The purpose of this paper is to empirically determine the causes of the worldwide diversity of inflation volatility. We show that higher degrees of political instability, ideological polarization and political fragmentation are associated with higher inflation volatility.